Peningkatan keterampilan dan minat menyanyikan tembang macapat pada siswa SMA melalui pemanfaatan aplikasi e-srambahan - Wahyudi, Ahmad Rizky; Darni, Darni; Andriyanto, Octo Dendy (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study aimed to improve the ability and interest of tenth-grade students at SMAN 13 Surabaya in performing tembang macapat within the context of Javanese language learning through the integration of the E-Srambahan application. The research employed the Kemmis and McTaggart classroom action research model. Data were collected through performance tests, observation, questionnaires, and interviews, involving 36 students from class X-2 with diverse cultural backgrounds. Quantitative analysis was conducted using SPSS version 25, including Levene’s Test and paired sample t-test, complemented by descriptive analysis. The findings revealed significant improvement in vocal performance, covering pleng (pitch accuracy), ngeng (rhythmic consistency), and greng (vocal strength). The students’ mean score increased from 64.7 (pre-cycle) to 74.3 (cycle I) and 83.2 (cycle II), while the mastery level rose from 25% to 91.7%. The paired sample t-test yielded a significance value of 0.000, confirming meaningful differences across cycles. The effectiveness of E-Srambahan was attributed to students’ improved interest and ability to imitate pitch, maintain rhythm, and enhance vocal projection. Challenges related to low self-confidence and limited vocal technique were successfully addressed through structured practice with the application. These results highlight the importance of integrating digital media grounded in local wisdom to enrich Javanese language education.